Biomimetic nanocarriers: integrating natural functions for advanced therapeutic applications - Hugo Felix Perini; Beatriz Sodré Matos; Carlo José Freire de Oliveira; Marcos Vinicius da Silva (Beilstein Journal of Nanotechnology)
Biomimetic nanocarriers, engineered to mimic the characteristics of native cells, offer a revolutionary approach in the treatment of various complex human diseases. This strategy enhances drug delivery by leveraging the innate properties of cellular components, thereby improving biocompatibility and targeting specificity. Biomimetic nanocarriers demonstrate significant advancements in drug delivery systems against cancer therapy, Alzheimer's disease, autoimmune diseases, and viral infections such as COVID-19. Here, we address the therapeutic applications of biomimetic nanocarriers and their promising strategy for personalized medicine.